Non-target estrogenic screening of 60 pesticides, six plant protection products, and tomato, grape, and wine samples by planar chromatography combined with the planar yeast estrogen screen bioassay - Mehl, Annabel; Seiferling, Sophia; Morlock, Gertrud E.; Justus Liebig University Giessen (My University, 2023)
For non-target residue analysis of xenoestrogens in food, sophisticated chromatographic–mass spectrometric techniques lack in biological effect detection. Various in vitro assays providing sum values encounter problems when opposing signals are present in a complex sample. Due to physicochemical signal reduction, cytotoxic or antagonistic effect responses, the resulting sum value is falsified. Instead, the demonstrated non-target estrogenic screening with an integrated planar chromatographic separation differentiated opposing signals, detected and prioritized important estrogenic compounds, and directly assigned tentatively the responsible compounds. Sixty pesticides were investigated, ten of which showed estrogenic effects. Exemplarily, half-maximal effective concentrations and 17β-estradiol equivalents were determined. Estrogenic pesticide responses were confirmed in six tested plant protection products. In food, such as tomato, grape, and wine, several compounds with an estrogenic effect were detected. It showed that rinsing with water was not sufficient to remove selected residues and illustrated that, though not usually performed for tomatoes, peeling would be more appropriate. Though not in the focus, reaction or breakdown products that are estrogenic were detected, underlining the great potential of non-target planar chromatographic bioassay screening for food safety and food control.
Keywords: ddc:630